Prefiguring houses in a traditional city: a case for Benin house types and characteristics - Ekhaese, Eghosa Noel; Amole, Bayo; Izobo-Martins, Oladunni (Journal of Architecture and Urbanism, 2018)
House mean different things to different people. House could be a dwelling, home, hut, place for; entertainment, rest, sleeping, receiving guest, and a palace. The interpretation of house as shelter makes it a basic necessities of life. Thus the focus of the paper is to identify and document house types in Benin by observing the physical characteristics and type’s classification from the organization and pattern of architectural plan documented. The study explored qualitative and quantitative approach using observations, descriptive frequency, architectural sketches, photographs and interview guide. The findings revealed a cross sectional characterising and classifying houses in Benin City, Nigeria which reflect the typical cross section structure of a traditional city. The result of study would however, influence professional in built environment and policy maker decision positively. First published online 28 December 2017